The Crime Of Assault On Wildlife From The Perspective Of Islamic Jurisprudence And Its Impact On Sustainable Development In The Kingdom Of Saudi Arabia - El-Sayed Abu El-Ala, Khaled Fouad (Journal of Neonatal Surgery, 2025)
The research aimed to define wildlife from the perspective of Islamic jurisprudence, the penalty for assault on wildlife, and to clarify the effects thereof from both the Sharia and legal perspectives. The Research relied on the descriptive method, and within that framework, employed the analytical approach. It resulted in many findings, the most prominent of which are as follows: Wildlife refers to forms of animal and plant life that are not subject to human intervention, and the concept includes wild creatures: any living or dead being that scientifically belongs to the animal or plant groups, excluding humans and domesticated or tame creatures. Protected areas are included. Wildlife plays a fundamental role in maintaining the natural balance of life. Means of proving assault on wildlife include inspection, expert opinion, confession, and evidence. Hunting is permitted in principle by legislation; however, obedience to the ruler is obligatory, and among the ruler’s prerogatives is the restriction of the permissible. Assault on wildlife constitutes a violation of legal provisions, and punishment may extend to fines, then imprisonment of varying terms, and fines which may reach into the millions. Preservation of wildlife encourages tourism, contributes to economic growth, and stimulates ambition to innovate in developing this field, which is the aim of sustainable development. Recommendations The researchers recommend the following: obedience to the ruler in matters related to the environment and otherwise, and the dissemination of a culture of wildlife protection.